Estimate of Radiosonde Dry Bias From Far‐Infrared Measurements on the Antarctic Plateau. Issue 6 (30th March 2018) - Rizzi, R.; Maestri, T.; Arosio, C.
Abstract: The experimental data set of downwelling radiance spectra measured at the ground in clear conditions during 2013 by a Far‐Infrared Fourier Transform Spectrometer at Dome‐C, Antarctica, presented in Rizzi et al. (2016, https://doi.org/10.1002/2016JD025341 ) is used to estimate the effect of solar heating of the radiosonde humidity sensor, called dry bias. The effect is quite evident comparing residuals for the austral summer and winter clear cases and can be modeled by an increase of the water vapor concentration at all levels by about 15%. Such an estimate has become possible only after a new version of the simulation code and spectroscopic data has become available, which has substantially improved the modeling of water vapor absorption in the far infrared. The negative yearly spectral bias reported in Rizzi et al. (2016, https://doi.org/10.1002/2016JD025341 ) is in fact greatly reduced when compared to the same measurement data set. Key Points: Downwelling radiance spectra measured during 2013 by an FTS Spectrometer at Dome‐C, Antarctica, are compared to simulations using improved total water vapor absorption in the far infrared The modeling improvement of the water vapor absorption in the far infrared makes evident the signature of the radiosonde dry bias effect and possible its estimation Accurate modeling in clear conditions is fundamental to derive clouds infrared properties in FIR microwindows